2021
DOI: 10.1111/brv.12789
|View full text |Cite
|
Sign up to set email alerts
|

Plant susceptible responses: the underestimated side of plant–pathogen interactions

Abstract: Plant susceptibility to pathogens is usually considered from the perspective of the loss of resistance. However, susceptibility cannot be equated with plant passivity since active host cooperation may be required for the pathogen to propagate and cause disease. This cooperation consists of the induction of reactions called susceptible responses that transform a plant from an autonomous biological unit into a component of a pathosystem. Induced susceptibility is scarcely discussed in the literature (at least co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 266 publications
0
35
0
Order By: Relevance
“…The induced host pectinases may promote cell wall remodeling [ 62 ], which may increase the amount of defense-activating pectic fragments to amplify the DAMP response. On the other hand, plant pectinases and cell-wall modification have been suggested to be susceptibility responses that are induced by virulent plant pathogens to promote symptoms in their susceptible host plant [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The induced host pectinases may promote cell wall remodeling [ 62 ], which may increase the amount of defense-activating pectic fragments to amplify the DAMP response. On the other hand, plant pectinases and cell-wall modification have been suggested to be susceptibility responses that are induced by virulent plant pathogens to promote symptoms in their susceptible host plant [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The function of sugar transporters may be important for the plant’s ability to mount an efficient defense, or it may be related to the ability of the bacteria to modulate sugar efflux of their host for their own benefit [ 67 ]. Redistribution of sugars and changes in the transport of water and nutrients have been identified as susceptibility responses affected by pathogens to create a suitable environment for pathogenesis [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some extensins (designated as LRX), containing an additional N-terminal domain composed of leucine-rich repeats (LRR), are considered important sensors that trace the state of PCW and transmit the signals via partner proteins [56,57]. Thus, breaking down or modifying extensins may not only weaken PCW but also influence the signaling processes of the host plant, leading to the repression of defense reactions or the induction of susceptible responses [58].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the GO analysis of the DEGs provide evidence that A. brassicicola seed infection caused increased expression of genes described to contribute to defense pathways, and on the other hand reduced the expression of genes involved in metabolic activity, growth and photosynthesis. Beyond the noted absence of inducing the JA pathway in germinating seeds, the identified responding pathways (Figure 2A), such as the induction of response to wounding and to catabolic process in seedlings and the repression of starch metabolism and cell wall biogenesis (Figure 2B) suggested that A. brassicicola in part would hijack the seed and seedling response to facilitate its colonization [43].…”
Section: Go Comparison Of Degs Between Healthy and A Brassicicola Inf...mentioning
confidence: 99%